Refinement of Miocene sea level and monsoon events from the sedimentary archive of the Maldives (Indian Ocean) - Betzler, C. (2018)
International Ocean Discovery Program (IODP) Expedition 359 cored sediments from eight borehole locations in the carbonate platform of the Maldives in the Indian Ocean. The expedition set out to unravel the timing of Neogene climate changes, in particular the evolution of the South Asian monsoon and fluctuations of the sea level. The timing of these changes are assessed by dating resultant sedimentary alterations that mark stratigraphic turning points in the Neogene Maldives platform system. The first four turning points during the early and middle Miocene are related to sea-level changes. These are reliably recorded in the stratigraphy of the carbonate sequences in which sequence boundaries provide the ages of the sea-level lowstand. Phases of aggradational platform growth give precise age brackets of long-term sea-level high stands during the early Miocene and the early to middle Miocene Climate Optimum that is dated here between 17 to 15.1 Ma. The subsequent middle Miocene cooling coincident with the eastern Antarctic ice sheet expansion resulted in a long-term lowering of sea level that is reflected by a progradational platform growth. The change in platform architecture from aggradation to progradation marks this turning point at 15.1 Ma.& para;& para;An abrupt change in sedimentation pattern is recognized across the entire archipelago at a sequence boundary dated as 12.9-13 Ma. At this turning point, the platform sedimentation switched to a current-controlled mode when the monsoon-wind-driven circulation started in the Indian Ocean. The similar age of the onset of drift deposition from monsoon-wind-driven circulation across the entire archipelago indicates an abrupt onset of monsoon winds in the Indian Ocean. Ten unconformities dissect the drift sequences, attesting changes in current strength or direction that are likely caused by the combined product of changes in the monsoon-wind intensity and sea level fluctuations in the last 13 Ma. A major shift in the drift packages is dated with 3.8 Ma that coincides with the end of stepwise platform drowning and a reduction of the oxygen minimum zone in the Inner Sea.& para;& para;The strata of the Maldives platform provides a detailed record of the extrinsic controlling factors on carbonate platform growth through time. This potential of carbonate platforms for dating the Neogene climate and current changes has been exploited in other platforms drilled by the Ocean Drilling Program. For example, Great Bahama Bank, the Queensland Plateau, and the platforms on the Marion Plateau show similar histories with sediment architectures driven by sea level in their early history (early to middle Miocene) replaced by current-driven drowning or partial drowning during their later history (Late Miocene). In all three platform systems, the influence of currents on sedimentations is reported between 11 and 13 Ma.